Distribution modeling of the long-tailed marmot (Marmota caudata) for objectives of directing field surveys and ground validation of the snow leopard (Panthera uncia) habitat quality - Tytar, V.; Hammer, M.; Asykulov, T. (Theriologia Ukrainica, 2019)
Marmots form a part of the diet of some endangered species such as the snow leopard (Panthera uncia), therefore the knowledge on their distribution and habitat preferences are crucial to the interest of the conservation and management of carnivores at high altitudes. Considering this, within a snow leopard project run by Biosphere Expeditions and NABU (Kyrgyzstan), surveys were carried out in summer field seasons of 2014–2019 to assess the distribution of the long-tailed marmots (Marmota caudata) in an area centered around the Karakol Mountain Pass (polygon centroid 74.83° E, 42.37° N) in the Kyrgyz Ala-Too Range. The presence of occupied marmot burrows was recorded using the location (cell) given by a grid, the code of which was displayed in a GPS. Using cells allows examination of data at a wider scale, so information is collected from different cells that are spread from each other, avoiding data autocorrelation. Environmental factors that may affect the spatial distribution of burrow systems were considered: land surface temperature (LST) in winter and summer, summer normalized difference vegetation index (NDVI), a Digital Elevation Model (DEM), and soil type data. The relationship between environmental factors and burrow records was analyzed using ecological niche models (Maxent) to predict the distributions of marmot burrows. The models performed well with average test AUC values of 0.939. The contribution orders of the variables in the models were summer NDVI and DEM, winter LST, summer LST, and soil type. The distribution of the suitable areas was largely (up to 38 % permutation importance) affected by summer NDVI. NDVI is an indicator of the feeding conditions of marmots and most of the records were distributed in areas with NDVI in summer ranging from 0.5 to 0.7. According to the prediction maps, suitable marmot habitat (> 0.5 predicted probabilities of occurrence) can occupy up to 40 % of study area. These maps are used to direct sampling efforts to areas on the landscape that tend to have greater predicted probabilities of occurrence and accomplish ground validation of snow leopard habitat quality. Бабаки складають частину раціону деяких зникаючих видів, зокрема таких як сніговий барс (Panthera uncia), тому знання про їхнє поширення та екологічні преференції мають вирішальне значення для справи збереження та природоохоронного управління хижими тваринами на великих висотах. Враховуючи це, в рамках проекту стосовно снігового барса, яким керують неурядові організації «Біосферні експедиції» та NABU (Киргизстан), влітку 2014–2019 рр. були проведені обстеження просторового розподілу довгохвостих бабак (Marmota caudata) в районі, зосередженого навколо гірського перевалу Каракол (полігонний центроїд 74.83° сх. д., 42.37° пн. ш.) на хребті Киргизського Ала-Тоо. Наявність зайнятих нір бабака фіксували за допомогою пристрою GPS зі завантанженою картою місцевості поділеною на комірки, кожна з яких має унікальний код. Використання комірок дозволяє отримувати дані в більш широкому масштабі, при цьому інформація збирається з різних комірок, віддалених одна від одної, і таким чином можна уникнути автокореляції даних. Були розглянуті екологічні фактори, які можуть впливати на просторовий розподіл нір: температура поверхні землі (LST) взимку та влітку, літній нормалізований диференційний вегетаційний індекс (NDVI), цифрова модель висоти (DEM) та дані про тип ґрунту. Взаємозв'язок між екологічними факторами та розподілом нір був проаналізований за допомогою моделей екологічної ніші (Maxent). Моделі показали добру відповідність, середні значення показника AUC для тестових даних склав 0,939. За внеском у модель змінні ранжуються в наступному порядку: літні NDVI та DEM, зимові LST, літні LST та тип ґрунту. На розподіл сприятливих для перебування бабаків територій найбільший вплив мав літній NDVI (до 38 % пермутаційної важливості). NDVI — це показник стану кормової бази бабаків і якраз більшість реєстрацій їхніх нір зроблено там, де NDVI коливається в межах 0,5–0,7. Згідно з картами прогнозування, сприятливе середовище перебування бабака (де ймовірність появи тварин > 0,5) може займати до 40 % площі дослідження. Ці карти використовуються для спрямування зусиль стосовно обстеження ділянок ландшафту на предмет виявлення бабаків та наземної верифікації якості угідь для перебування снігового барса.